2020
DOI: 10.3390/ijms21030985
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Orchid Protocorm-Like Bodies: Mass Propagation, Biotechnology, Molecular Aspects, and Breeding

Abstract: The process through induction, proliferation and regeneration of protocorm-like bodies (PLBs) is one of the most advantageous methods for mass propagation of orchids which applied to the world floricultural market. In addition, this method has been used as a tool to identify genes of interest associated with the production of PLBs, and also in breeding techniques that use biotechnology to produce new cultivars, such as to obtain transgenic plants. Most of the molecular studies developed have used model plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 131 publications
3
71
1
Order By: Relevance
“…In addition, some results from orchid studies using CRISPR-Cas systems for genome editing have been recently released. Although plants belonging to the Orchidaceae, the second largest family of flowering plants, currently occupy an important position in global commercial floriculture crop production based on economic value [59], limited genomic sequence information on orchid species is available: genome information is available for Dendrobium catenatum [5], Dendrobium officinale [6], Gastrodia elata [60], Phalaenopsis aphrodite [61], and Phalaenopsis equestris [12]. Moreover, only a couple of studies involving genome editing by CRISPR-Cas systems have been reported in orchids.…”
Section: Current Status Of Genome Editing In Ornamental Plantsmentioning
confidence: 99%
“…In addition, some results from orchid studies using CRISPR-Cas systems for genome editing have been recently released. Although plants belonging to the Orchidaceae, the second largest family of flowering plants, currently occupy an important position in global commercial floriculture crop production based on economic value [59], limited genomic sequence information on orchid species is available: genome information is available for Dendrobium catenatum [5], Dendrobium officinale [6], Gastrodia elata [60], Phalaenopsis aphrodite [61], and Phalaenopsis equestris [12]. Moreover, only a couple of studies involving genome editing by CRISPR-Cas systems have been reported in orchids.…”
Section: Current Status Of Genome Editing In Ornamental Plantsmentioning
confidence: 99%
“…Orchid plants belong to family Orchidaceae which represents one of the two largest plant families (6-11% of flowering plant species), which include 736 -899 genera, 27,800 species and more than 100,000 hybrids worldwide (Cardoso et al 2020). Orchids also have several benefits besides its unquestionable importance from the botanical and ecological aspects, the most important cutflowers in the world commercial floriculture and for medicinal purposes (e.g., some species of the genera Dendrobium, Gastrodia and Bletilla) (Cardoso et al 2020). It is reported that orchids have a significant share of the annual sales of the global flower trade more than 4 billion US $ (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of orchid species do not have nutritional reserves and the endosperm is absent from the mature orchid seeds (Yeung et al 2018). Both the seedlings and seed embryos are mainly depending on the symbiosis food relationship with the mycorrhizae, which have the ability to nutritionally supply these plant species at early germination and for a long time till the complete establishment of the seedling under the natural environments (Cardoso et al 2020).The micro-propagation and traditional breeding have been used in several orchids to get the cut flowers and/or potted plants in horticultural markets (Wang et al 2019). Due to the growth nature of orchid roots, their rooting difficulty is one of the main problems facing propagation and production of orchids (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, effective and efficient technologies for mass orchid propagation must be developed to meet commercial demands for successful orchid conservation [4]. Therefore, it is necessary to make efforts to conserve rare orchids and increase the production of black orchid seeds with plant propagation, both generative and vegetative propagation by in vitro culture [5] Currently available cultivation techniques for in vitro production of orchid seedlings or plantlets include asymbiotic germination and micropropagation techniques, which can be employed for the large-scale production of clonal plantlets [6]. Efforts to rescue and propagate black orchids have employed in vitro culture techniques, which enable rapid propagation of explants, preservation of germplasm and multiplication of plants that are difficult to reproduce conventionally [7].…”
Section: Introductionmentioning
confidence: 99%